KEBIJAKAN ZONASI DALAM TIMBANGAN TEORI JUSTICE AS FAIRNESS JOHN RAWLS - Latifah, Nafsi; Nurmaini, Nurmaini; Putra, Muhammad Indra Eka; Hidayat, Hafiz; As Sayfullooh, Istiqomah (Prodi PAI STIT Sunan Giri Bima, 2024)
In order to improve equitable access to education, the government implemented a zoning policy in the admission of new students from kindergarten to senior high school level. This research is conducted to explore the alignment between the zoning policy and the theory